2004
DOI: 10.2527/2004.824973x
|View full text |Cite
|
Sign up to set email alerts
|

A resource allocation model describing consequences of artificial selection under metabolic stress

Abstract: Long-term selection on production results in increased environmental sensitivity. This often is expressed through decreased fertility and increased health problems. The phenomenon has been described in all common farm animal species. One theory is that potential resource intake is insufficient to express production potential. Additional resources are drawn away from fitness-related traits, such as fertility and health, to further increase observed production. In addition, resources for maintaining fitness depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 26 publications
1
38
0
2
Order By: Relevance
“…It has been observed that selection for economically important traits tends to increase the susceptibility to environmental factors [44, 45]. In our study, ancestral mutations classified as benign in genes involved in immune related genes such as IL12RB2 and STAB1 , were observed in several local pigs.…”
Section: Discussionmentioning
confidence: 52%
“…It has been observed that selection for economically important traits tends to increase the susceptibility to environmental factors [44, 45]. In our study, ancestral mutations classified as benign in genes involved in immune related genes such as IL12RB2 and STAB1 , were observed in several local pigs.…”
Section: Discussionmentioning
confidence: 52%
“…Substantial differences exist between the nutrient allocation rules adopted in different modelling studies [3], [19], [34]. The rule chosen here implies that resource allocation partly depends on the host genetic potential for growth and disease resistance and varies over time according to the physical state of the animal [19], [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous simulation studies of selection experiments suggest that the relationship between production and immune traits in a population depends strongly on the physiological status of the animals at the time of selection as well as on the genetic relationship (e.g. pleiotropy or linkage) between production and resistance traits [33], [34]. However, these studies have assumed that the performance-resistance relationship is mainly determined by host genetics and the infectious challenge, whereas the potential influence of the nutritional environment has been ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental sensitivity was generally shown to increase in response to selection for high phenotypic values when G × E interaction is present [5, 6, 44]. According to Jinks and Connolly [45], this should be true especially when selection for a high phenotypic value occurs in an environment that produces a phenotype with a higher value compared to another environment (synergistic selection).…”
Section: Discussionmentioning
confidence: 99%